53 Trends in long-term demand for emergency medical services in victoria, australia. (16th April 2018) - Andrew, Emily; Nehme, Ziad; Bernard, Stephen; Cameron, Peter; Smith, Karen
Abstract : Aim: Although emergency medical service (EMS) utilisation is increasing internationally, the factors driving this increase have not been well quantified using a large EMS dataset. We sought to describe long-term trends in EMS utilisation in Victoria, Australia. Method: We conducted a retrospective observational study of consecutive patients presenting to the state-wide EMS in Victoria, Australia between 01/01/2010 and 31/12/2015. We calculated incidence rates of EMS presentations using Victorian population estimates, and conducted time-series regression analysis, adjusted for temporal trends and population size. Results: A total of 2, 923, 815 EMS patient presentations were included. Patient presentations grew by an average of 4.3% per annum, compared with 2.0% annual growth in the Victorian population. Age-specific incidence was highest among patients aged ≥81 years although this did not grow significantly over time (2010: 517 presentations/1000 person-years vs 2015: 533/1000 person-years, p=0.8). However, the median age of patients decreased over time (2010: 60.2 vs 2015: 58.7, p<0.001). Among emergency ambulance-attended patients, 51.5% were recorded as having no comorbidities according to the Charlson Comorbidity Index, and this proportion remained steady over time (2010: 51.5% vs 2015: 51.8%). The rate of medical intervention by paramedics decreased over time (2010: 59.5% vs 2015: 46.8%, p<0.001), as did the rate of transportation to hospital (2010: 79.1% vs 2015: 77.4%, p<0.001). According to adjusted analyses, a population increase of 1000 people aged >65 years was associated with a 0.4% increase in daily EMS demand (p=0.005). Conclusion: The profile of patients presenting to EMS is changing over time, with the median age decreasing and fewer patients requiring active intervention. Conflict of interest: None Funding: None